First Record of an Invasive Encrusting Bryozoan: Watersipora subtorquata (d’Orbigny, 1852) in Colombo Port, Sri Lanka. - Marasinghe, K.; Ranatunga, K.; Chandrashekar, A.; Weerasinghe, R. (My University, 2016)
Attached

Investigations on marine biological invasions have become an important field of study due to its enormous effect on ecology, economy and human health. Fouling on ship hulls considered to be one of the most common pathways of introducing non indigenous species (NIS) across the oceans.The present study was conducted in eight sampling locations within Colombo Port. Biofouling aggregates were collected using artificial settlement plates (10cm x 10cm) submerged in four depths. The first set was lm below the water surface and others settled in lm increments. Monthly samples were collected from October 2014 to July 2015 from both replacing and permanently settled collectors. Species were identified microscopically, observing their fine morphological features using stereomicroscopes. Eight morphologically dissimilar encrusting bryozoans were recorded. The most promising finding is the first record of highly invasive encrusting bryozoan, Watersipora subtorquata. They were recorded in two of the sampling locations. In New Pilot Station (NPS), they were recorded at 2m depth covering 12.5% of the panel area and Bandaranayake Quay (BQ) at lm depth covering 2.19% of the panel area. W. Subtorquata is an encrusting foliaceous colonial bryozoans affiliated to the family Watersiporidae belong to the suborder Ascophora. The colony is dark or black with bright orange outer growing edge. The colony consists with comparatively large and distinct zooecia with numerous pores and distinct mushroom shaped operculum. This species is well recognized as highly invasive in many parts of the world and they facilitate the dispersion of other invasive organisms via providing non toxic substrates to settle in, compete with native bryozoans and other fouling organisms subsequently altering